Partisipasi Karyawan pada Kondisi Bekerja dari Rumah di Masa Pandemi Covid-19 - Bimo Taufan Devara; Nathanael Christian; Rafi Achas Muhammad; Yuliana Sanni (Indonesian Business Review, 2022)
The purpose of this study was to determine the level of employee participation in an industry that allows employees to work from home during the COVID-19 pandemic in Indonesia. The research was conducted through a survey by distributing questionnaires using Indonesian. Obtained data from 301 employees who work from home throughout Indonesia. This research illustrates that of the 4 (four) types of variables that are considered to affect the level of employee participation, one variable, namely autonomy, does not significantly affect the level of employee participation. This study makes an important contribution by empirically investigating employees in Indonesia in assessing the amount of work participation when doing Work From Home during the COVID-19 pandemic.